X-band and Ku-band PIN diode loaded reflectarray unit cells with adaptive frequency switching - Inam Abbasi, Muhamamad; Dali Khan, Sher; Hashim Dahri, Muhammad; Mohd Ibrahim, Imran; Hafizah Sulaiman, Noor (Institute of Advanced Engineering and Science, 2025)
The fast advancement of intelligent new applications has led to the creation of high-performance antennas. Reflectarrays (RAs), also known as planar reflectors, are seen as promising antennas for several such modern-day applications. This work presents a comprehensive investigation of frequency switchable RA antennas operating in the X-band and Ku-band frequency ranges. Various strategic configurations of combined slots have been suggested, using integrated P-layer, I-layer, and N-layer (PIN) diodes, with the purpose of creating unit cells in RAs that may switch frequencies and exhibit a gradual change in phase distribution. The frequency variation achieved in X-band for the ON state of PIN diodes is from 8.13 GHz to 11.69 GHz, whereas for the OFF state it is from 8.13 GHz to 11.68 GHz. Similarly, for Ku-band ON and OFF states of PIN diodes provided frequency variations of 13.6 GHz to 17.1 Ghz and 12.8 Ghz to 16.6 GHz respectively. Frequency tunability of 0.85 GHz and 0.72 GHz has been successfully achieved in X-band and Ku-band.